2021
DOI: 10.3390/app11073240
|View full text |Cite
|
Sign up to set email alerts
|

Elastography—A Bona Fide Non-Invasive Method for Assessing Non-Alcoholic Fatty Liver Disease in Children

Abstract: Pediatric obesity has become a major public health problem worldwide, resulting in a wide spectrum of systemic complications. Liver disease associated with obesity, also known as nonalcoholic fatty liver disease (NAFLD), is currently the most common chronic liver condition in children. Therefore, its timely and proper diagnosis is essential for preventing further development of cirrhosis. Multiple studies focused on identifying the most accurate non-invasive diagnostic method for liver fibrosis or cirrhosis. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 121 publications
(131 reference statements)
0
4
0
Order By: Relevance
“…Using the FLI, the study found that the prevalence of fatty liver disease (FLI ≥ 60) in Korean adults aged 20 years and older increased from 13.3% in 2009 to 15.5% in 2017. This increase was particularly prominent among men and the younger age group (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39). Furthermore, the study found that people with T2DM had the highest prevalence of fatty liver disease, with a steep increase seen in the young T2DM population.…”
Section: Description Of Studies That Appreciated the Diagnostic Role ...mentioning
confidence: 85%
See 1 more Smart Citation
“…Using the FLI, the study found that the prevalence of fatty liver disease (FLI ≥ 60) in Korean adults aged 20 years and older increased from 13.3% in 2009 to 15.5% in 2017. This increase was particularly prominent among men and the younger age group (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39). Furthermore, the study found that people with T2DM had the highest prevalence of fatty liver disease, with a steep increase seen in the young T2DM population.…”
Section: Description Of Studies That Appreciated the Diagnostic Role ...mentioning
confidence: 85%
“…Thus, the most well-known methods are liver elastography and blood markers of fibrosis. Elastography measures the stiffness of the tissues, and the assessment of liver fibrosis is based on ultrasound, which measures only a small component of the stiffness of the tissues [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…There are limitations for using ALT for the assessment and management of pediatric NAFLD, but ALT is still widely used because it is cost-effective and noninvasive compared to other methods such as liver biopsy and MRI due to the need of sedation and increased radiation exposure with CT scan. Conventional ultrasound is not accurate enough for the assessment of NAFLD in children due to interobserver variability, and newer noninvasive methods such as elastography are not yet widely available, and there are still limitations in the pediatric population [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Examples of wearables in the market are CareUp or InstaBP, which range in precision and usability 322,335–337 . (E) Examples of elastography modalities available in the market: Transient elastography (TE, left), shear wave elastography (SWE, center), and magnetic resonance elastography (MRE, right) (Adapted from reference 338–340). (F) ARTIDIS tumoral biopsy in breast cancer and indentation scheme.…”
Section: Clinical Practice and Development Of New Technologies In Mec...mentioning
confidence: 99%